Management of Aberrant Labial Frenum: Series of Cases - Bagchi, Suchi Suvra; Sarkar, Puja; Bandyopadhyay , Prasanta (Advancement and New Understanding in Medical Science Vol. 4, 2024)
This chapter describes three case reports of different frenectomy techniques used for management of aberrant frenum. The frenum is a mucous membrane fold that attaches the lip and the cheek to the alveolar mucosa, the gingiva, and the underlying periosteum. The procedure of complete removal of the frenum, including its attachment to the underlying bone is known as frenectomy while the incision and the relocation of the frenal attachment are known as frenotomy. A frenum that encroaches on the margin of the gingiva may interfere with plaque removal and cause tension. Any of the modification procedures can be used to remove an abnormal frenum, however proper technique selection based on the type of frenal attachment can result in a functional and aesthetic result.